Assessment of integrated MSW management using multicriteria analysis in São Paulo City - Rodrigues, E. [UNESP]; Mondelli, G. (Springer Nature, 2021)
The environmental concern with the treatment and final disposal of municipal solid waste (MSW) generated in cities has increased worldwide. In São Paulo, the largest Latin America’s city, the landfills use is preponderant and initiatives that incorporate treatment technologies that recover recyclable materials, compost, and generate energy are incipient. In this context, the main objective of this paper is to assess the treatment technologies for integrated MSW management and propose the optimal scenario that increases materials recovery and reduce the current landfill disposal, with the objective of postponing its lifetime. To achieve the result proposed, five scenarios were modeled and compared with the current scenario, which is (1) 2% of selective collection and 98% to the landfill. The other scenarios were: (2) Scenario 1 added by 4 mechanical biological treatment units (MBT); (3) Fivefold increasing of the selective collection, added by 2 Thermal Treatment Units (WtE); (4) 2% of selective collection, 2 MBTs and 2 WtEs; and (5) same of Scenario 2, but without compost sale. Considering environmental, financial, social, and technical factors of each scenario, the TOPSIS method was used, which orders the preference for similarity of the ideal solution. As a result, the Scenario 2 was the optimal solution, diverting 70% of MSW from landfill.
Keywords: Analytical Hierarchy Process (AHP); Material Recovery Facility (MRF); Mechanical Biological Treatment (MBT); Multicriteria Decision Making (MCDM); Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS); Waste to Energy (WtE)